Linking Magma Storage and Ascent to Eruption Volume and Composition at an Arc Caldera. Issue 14 (14th July 2020) - Miller, David; Bennington, Ninfa; Haney, Matthew; Bedrosian, Paul; Key, Kerry; Thurber, Clifford; Hart, Laney; Ohlendorf, Summer
Abstract: Conceptual models of magma storage and transport under calderas favor a connected system of sills and dikes. These features are individually below the resolution of standard seismic tomography, but radial seismic anisotropy can reveal where they exist in aggregate. We model radial anisotropy at Okmok caldera, Alaska, to demonstrate the presence of a caldera‐centered stacked sill complex and surrounding dike system. We show that ascending magma, inferred from seismicity, either intersects the sill complex, resulting in a larger volume eruption of evolved magma, or bypasses the overlying sill complex via dikes, resulting in a low‐volume mafic eruption. Our results exemplify how the locations of magma storage and paths of transport impact eruption size and composition. As this type of crustal storage is likely common to many calderas, this analysis offers a potential new framework for volcano observatories to forecast the size of impending eruptions. Plain Language Summary: Okmok caldera, in the central Aleutian Arc, has erupted approximately every decade for the last century and represents a notable hazard to the trans‐Pacific air traffic routes that overlie it. We deployed a temporary array of seismic instruments to supplement Okmok's existing seismic network. Modeling these seismic data, we identify a central region of magma storage at the volcano arranged in horizontal sheets (sills) surrounded by an adjacent ring of vertical sheets of cooled magma (dikes). Using the spatial patterns of earthquakes, we infer paths of magma transport in relation to these structures. For the 2008 Okmok eruption, we show that deeper, silica‐poor magma moved through and mobilized more silica‐rich magma stored in the shallow central sill region. This resulted in the 2008 eruption being larger and more explosive relative to the last century. In a typical historic eruption, by contrast, we conclude that the deeper magma source ascended through the dike system and bypassed the sill region, leading to smaller, silica‐poor eruptions. We suggest that the analysis presented in this study is a potential new framework for forecasting volcanic eruption size and may be of use to volcano observatories worldwide. Key Points: Okmok caldera is underlain by radially anisotropic velocity structures indicating a central sill complex and a surrounding ring of dikes The path of magma through or around the central stacked sill complex can control the volume and composition of erupted magmas